PENGEMBANGAN “MAS NOVEL” BERBASIS ETNOMATSAINS UNTUK MENANAMKAN SIKAP PEDULI LINGKUNGAN SISWA SEKOLAH DASAR - Ema Butsi Prihastari; Ratna Widyaningrum (Universitas Muhammadiyah Surakarta, 2018)
Abtract- This development research aims to produce a product namely fotonovela on mathematics and science learning as media like a comics that associated with the local wisdom in order to instill a students’ environtmentaly caring character. This study according to Gravemeijer Cobb (2006) has 3 steps: 1) preparation of research, 2) design experiment, and 3) restropspective analysis. The population of the research is all student’ elemetary school in Distric Laweyan. The sampling tecnique using purposive sampling. Laweyan Elementary School and Djama’atul Ichwan is selected.The results of material expert validation consist of suitability in K13 theme, the accuracy of the material, systematic, up to date material, and the material increase the competence of mathematics and science students obtained a score of 3.7 with the category very good. Meanwhile, the results of the validation of experts media include variations in presentation, readability, implementation, thorough look, illustrated score 3.5 (good). Then, the results of the response of teachers and students there are above 70%. So it can be concluded that MAS NOVEL (Mathematic and Science Fotonovela) viable for use in thematic learning in elementary school.